2013
DOI: 10.1021/jz402186w
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Fluctuations in Helical Propulsion: How Small Can a Propeller Be

Abstract: Helical propulsion is at the heart of locomotion strategies utilized by various natural and artificial swimmers. We used experimental observations and a numerical model to study the various fluctuation mechanisms that determine the performance of an externally driven helical propeller as the size of the helix is reduced. From causality analysis, an overwhelming effect of orientational noise at low length scales is observed, which strongly affects the average velocity and direction of motion of a propeller. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 39 publications
6
52
0
Order By: Relevance
“…In this section of our review, we discuss the range of dimensions in which Brownian motion may neglected, without going into further details of how the effects should be incorporated. Schamel et al (2014) found that 0.40-µm nanoscrews experience strong diffusion and are unable to propel effectively in pure water, in line with the observation that propellers below the length of 0.90 µm are dominated by Brownian motion and directional motion is not discernible (Ghosh et al 2013). For bacterial cells smaller than 1 µm, simulations which ignore Brownian motion leads to results that contradict microscopy observations, regardless (Li et al 2008).…”
Section: Brownian Motionmentioning
confidence: 54%
“…In this section of our review, we discuss the range of dimensions in which Brownian motion may neglected, without going into further details of how the effects should be incorporated. Schamel et al (2014) found that 0.40-µm nanoscrews experience strong diffusion and are unable to propel effectively in pure water, in line with the observation that propellers below the length of 0.90 µm are dominated by Brownian motion and directional motion is not discernible (Ghosh et al 2013). For bacterial cells smaller than 1 µm, simulations which ignore Brownian motion leads to results that contradict microscopy observations, regardless (Li et al 2008).…”
Section: Brownian Motionmentioning
confidence: 54%
“…A closed-loop control of microrobots is necessary for precise motion in presence of perturbations generated by thermal noise [80], or drifting due to boundary effects [35,81,82]. A robust and efficient control system is required for microrobots, because the high sensitivity of the micro-systems to environmental variables, and the high velocities at the microscale.…”
Section: Closed-loop Controlmentioning
confidence: 99%
“…As explained in [21], "Nonholonomic systems are, roughly speaking, mechanical systems with constraints on their velocity that are not derivable from position constraints." All the lateral motions applied on a helical swimmer generated by thermal noise [16], or drifting due to boundary effect [17] can be considered as a perturbation, and should be corrected. Compensation of thermal noises is both a motivation of the closed-loop control and a major technical challenge.…”
Section: Control Architecturementioning
confidence: 99%
“…A closed-loop control of helical swimmers is necessary for precise motion in the presence of perturbations generated by thermal noise [16] or drifting due to boundary effects [17]. The aim of this paper is to control a magnetic-actuated helical swimmer using visual feedback.…”
mentioning
confidence: 99%